The outcome of latent phase vs. Active phase admission to labour room of low risk nulliparous women in labour - Albassam, Anwar N. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: the first stage ,labour is divided into early (latent phase )when uterine contractions are irregular and cervical effacement and dilatation are gradual, while the active phase of labour commences when cervical dilatation reaches (4) cm .and uterine contractions are more powerful . Our aim from this study is to see the effect of the timing of admission to labour room on mode of delivery and foetal outcome.Patients and method: 240 nulliparous women at term pregnancy were diagnosed as labour pain and admitted to Baghdad Teaching Hospital from the first of January to the end of December 2006, they were followed during their course of labour to see the effect of admission to the labour room in latent phase in comparison to those in active phase of labour on the mode of delivery and fetal outcome.Results: Rate of C/Section was significantly higher in those admitted in the latent phase (group 1) than those in active phase [group2] (65% vs16.6%) Major cause of C/Section in group (1) was dystocia (65.3%) while in the group (2) was fetal distress (55%) Rate of C/Section among women whose labour was augmented in group (1) greater than group (2) (74% vs20%)Conclusion: Later admission to labour room increased the rate of spontaneous vaginal delivery in low risk nulliparous women